Genomic signatures of local adaptation reveal source-sink dynamics in a high gene flow fish species - Cure, K.; Thomas, L.; Hobbs, Jean-Paul; Fairclough, D.; Kennington, W. (Nature Publishing Group, 2017)
Understanding source-sink dynamics is important for conservation management, particularly when climatic events alter species' distributions. Following a 2011 'marine heatwave' in Western Australia, we observed high recruitment of the endemic fisheries target species Choerodon rubescens, towards the cooler (southern) end of its distribution. Here, we use a genome wide set of 14 559 single-nucleotide polymorphisms (SNPs) to identify the likely source population for this recruitment event. Most loci (76%) showed low genetic divergence across the species' range, indicating high levels of gene flow and confirming previous findings using neutral microsatellite markers. However, a small proportion of loci showed strong patterns of differentiation and exhibited patterns of population structure consistent with local adaptation. Clustering analyses based on these outlier loci indicated that recruits at the southern end of C. rubescens' range originated 400 km to the north, at the centre of the species' range, where average temperatures are up to 3 °C warmer. Survival of these recruits may be low because they carry alleles adapted to an environment different to the one they now reside in, but their survival is key to establishing locally adapted populations at and beyond the range edge as water temperatures increase with climate change.